Clinical Management of Equine Piroplasmosis - Dodiya, Piyush G.; Patel, Jayesh S.; Parmar, Vijay L.; Kalariya, Vinay A.; Singh, Vivek K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Total 200 cases of horses presented at the Veterinary Clinical Complex of the College of Veterinary Science & AH, Junagadh were screened  for equine piroplasmosis. Out of which, 9 (4.50%) were confirmed positive based on classical clinical signs and Giemsa-stained blood  smears. Hematological examination was conducted in all equine piroplasmosis positive horses, which revealed significant decrease  in RBCs, Hb, PCV, MCHC and thrombocytes, and no significant alteration in total and differential leukocyte count. The confirmed cases  were successfully treated with buparvaquone @ 4 mg/kg deep intramuscular along with supportive therapy for 1 to 3 weeks.
Keywords: Equine piroplasmosis; Hemoglobinuria; Icterus; Puparvaquone; Theileria equi